Sonography of the bicipitoradial bursa: A short pictorial essay - Draghi, F. (Elsevier, 2012)
Serous bursae consist of a synovial membrane enveloping a film of liquid. They are located at interfaces between moving structures where friction must be reduced. The bicipitoradial bursa lies between the distal tendon of the biceps brachii, which it surrounds, and the radial tuberosity. It is a relatively large bursa, with dimensions ranging from 2.4 to 3.9 cm. It sometimes presents septation. It does not communicate with the joint cavity, but it may communicate with the interosseous bursa of the elbow. Regardless of its cause, bicipitoradial bursitis presents as a mass in the cubital fossa and/or with neurological symptoms (sensorial and/or motorial) caused by compression of the radial nerve. On ultrasonography, the inflamed bursa is visualized as an anechoic formation surrounding the distal biceps tendon. In addition to its role in diagnosing the bursitis, sonography can provide information about radial nerve injury (in the presence of macroscopic damage), and it can also be used for guidance during intrabursal injections.